Defined metabolic states shape T cell fate and function across culture conditions - Sylvester, Kayla; Karassina, Natasha; Lauer, Anthony C.; Vidugiris, Gediminas; Vidugiriene, Jolanta (Frontiers in Immunology, 2025)
IntroductionT cell metabolism is a key determinant of immune function and therapeutic efficacy, yet current expansion protocols often neglect how culture conditions influence metabolic programming. We employed a modular, low-input bioluminescent assay platform to profile how media, activation strength, and metabolic perturbation define metabolic trajectories that persist through early expansion and influence downstream outcomes.MethodsA multifactorial experimental design was used to evaluate early T-cell activation across media (ICXF, TexMACS, RPMI+FBS) and activators (TransAct, Dynabeads, ImmunoCult). Low-input bioluminescent assays were used to quantify metabolic cofactors (ATP, NAD+, NADP(H)), reducing capacity, and nutrient usage (glucose, lactate, malate). Conditions that yield metabolically distinct phenotypes were selected for deeper analysis of proliferation, cytokine secretion, cytotoxicity, and flow cytometric profiling. To validate and functionally confirm these phenotypes, pathway-specific metabolic inhibitors were introduced in follow-up experiments.ResultsBy measuring intracellular ATP, NAD+, NADP(H), reducing capacity, and nutrient flux, we identified media- and activation-specific metabolic states that emerged upon T-cell activation and persisted through early expansion. ICXF with TransAct promoted a glycolytic, NAD-rich phenotype associated with rapid expansion. In contrast, TexMACS with ImmunoCult supported oxidative metabolism, enriched for TSCM-like cells, and enhanced cytotoxicity despite slower growth. Early lactate levels strongly predicted downstream expansion (r = 0.68, p < 0.0001), highlighting glycolytic activity as a key determinant of proliferative potential. Functional validation with pathway-specific inhibitors revealed media-dependent vulnerabilities, highlighting distinct metabolic wiring.ConclusionThis approach enables predictive, multiplexed metabolic profiling using minimal sample input and offers a scalable strategy to optimize T-cell manufacturing for memory enrichment and cytotoxic potency.